Health as a value in the formation of student-centered motivation of students to physical education - Gruzhevsky, V.A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: definition of motivational value to the health needs of students, due to the region of residence. Material : the study involved 780 students: girls – 522, boys - 258. Motivational needs for personal health were determined by questionnaire. Taken into account location and ethnic features. Results : it was proved that the majority of students have a low level of physical health. Defined regulatory role of personal motivation of students in relation to health. She said the motive of the desire to be healthy, uncertainty as to personal health, motivated desire to bad habits. The girls of the main regions of the Crimea was a state of uncertainty to personal health. In the ethnic group of girls - the pursuit of better health. The young men of the Crimean regions and ethnic groups dominant motif found desire for personal health. Conclusions : it was determined that the training sessions with the inclusion of elements ethnopedagogical orientation changed motivational needs of young people. Significantly increased motivation need to be healthy, it became less of students with an uncertain attitude towards personal health, decreased motivation to bad habits.